2013
DOI: 10.1016/j.neuroimage.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Traveling waves and trial averaging: The nature of single-trial and averaged brain responses in large-scale cortical signals

Abstract: Analyzing single trial brain activity remains a challenging problem in the neurosciences. We gain purchase on this problem by focusing on globally synchronous fields in within-trial evoked brain activity, rather than on localized peaks in the trial-averaged evoked response (ER). We analyzed data from three measurement modalities, each with different spatial resolutions: magnetoencephalogram (MEG), electroencephalogram (EEG) and electrocorticogram (ECoG). We first characterized the ER in terms of summation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 66 publications
5
102
0
Order By: Relevance
“…On the other hand, reliable estimation of evoked potentials is possible only after averaging of many trials. In the averaging, task-relevant information may be lost (Alexander et al, 2013(Alexander et al, , 2015. In contrast, the time-frequency analysis can reliably be done on single trials, which allows to study how experimental stimulation modulates ongoing brain activity.…”
Section: Merits Of Frequency Vs Time Domain Analysismentioning
confidence: 99%
“…On the other hand, reliable estimation of evoked potentials is possible only after averaging of many trials. In the averaging, task-relevant information may be lost (Alexander et al, 2013(Alexander et al, , 2015. In contrast, the time-frequency analysis can reliably be done on single trials, which allows to study how experimental stimulation modulates ongoing brain activity.…”
Section: Merits Of Frequency Vs Time Domain Analysismentioning
confidence: 99%
“…In this direction, the results of a study by Alexander et al (2013), suggested that phase topography and phase gradient, rather than trial average, may be more relevant to the understanding of event-related activity. The use of similar methodological approaches may provide a promising tool for future research in order to further characterize the neural mechanisms involved in perceptual grouping.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Traveling waves have also been observed in the scalp EEG, although there is some debate as to whether it reflects the propagation of cortical activity or if it can be explained by volume conduction of the activity from a few neuronal sources (Hughes, 1995;Nunez et al, 2001;Alexander et al, 2013). Recent work has demonstrated cross-frequency interactions in which the amplitude of gamma band activity is coupled to the phase of alpha activity (Osipova et al, 2008;Voytek et al, 2010;Spaak et al, 2012).…”
Section: Introductionmentioning
confidence: 99%